Bilateral loss of cortical SEPs predict severe MRI lesions in neonatal hypoxic ischemic encephalopathy treated with hypothermia. Issue 1 (January 2018) - Suppiej, Agnese; Cappellari, Ambra; Talenti, Giacomo; Cainelli, Elisa; Di Capua, Matteo; Janes, Augusta; Longo, Daniela; Mardari, Rodica; Marinaccio, Cristina; Pro, Stefano; Sciortino, Paola; Trevisanuto, Daniele; et al.
Highlights: Bilaterally absent SEPs predict MRI injury in infants cooled for hypoxic ischemic encephalopathy. Normal MRI is usually associated with normal SEPs. Therapeutic hypothermia does not seem to affect prognostic reliability of SEPs. Abstract: Objective: The introduction of therapeutic hypothermia for neonatal hypoxic-ischemic encephalopathy calls for reevaluation of the prognostic role of somatosensory evoked potentials (SEPs). Methods: Among 80 consecutive neonates undergoing hypothermia for hypoxic-ischemic encephalopathy, 58 performed SEPs and MRI at 4–14 days of life and were recruited in this multicenter study. SEPs were scored as: 0 (bilaterally/unilaterally recorded N20) or 1 (bilaterally absent N20). The severity of brain injury was scored using MRI. Results: Bilaterally absent N20 was observed in 10/58 neonates (17%); all had moderate/severe MRI abnormalities; 36/48 neonates (75%) with score 0 at SEPs had normal MRI. The positive predictive value of SEPs on MRI outcome was of 1.00, while the negative predictive value 0.72, sensitivity 0.48, specificity 1.00, with an accuracy of 0.78 (p < .001). Conclusions: Bilateral absence of cortical SEPs predicts moderate/severe MRI pattern of injury. Significance: Therapeutic hypothermia does not seem to significantly affect prognostic reliability of SEPs.